(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Graphic design has become a necessity in various areas of life, including branding and website design. Today, graphic design has become an important part of various sectors of life, especially to support the economic and marketing sectors. Therefore, the ability and skills of graphic design and visual arts are very much needed. This is an opportunity to equip young people with graphic design skills. The results of a survey conducted by the community service team showed that teenagers in Kalikejambon village have a high interest in graphic design art. So it is necessary to make real efforts to equip teenagers in Kalikejambon village with graphic design skills. Therefore, in this community service activity, graphic design training and mentoring were carried out using the Canva application to improve the creativity of teenagers in Kalikejambon village. The method of implementing community service is in the form of lectures providing material directly by resource persons to partners. Based on the results of this activity, it is known that this training and mentoring are effective in improving the graphic design skills of participants. This training and mentoring also fosters the motivation of teenagers in Kalikejambon village in doing graphic design visual arts. These positive results are in line with several previous research activities which show that training and mentoring have a positive impact on graphic design knowledge and skills. In addition, training and mentoring activities also increase the motivation of activity participants to work through graphic design media.